Short inter-stimulus intervals can be used for olfactory electroencephalography in patients of varying olfactory function. (5th November 2017) - Whitcroft, K.L.; Aziz, M.; Croy, I.; Schriever, V.; Hummel, T.
Highlights: The clinical utility of chemosensory EEG is limited by long acquisition times. Long acquisition times are attributable to the duration of the inter-stimulus interval (ISI) Use of short ISIs in chemosensoryW EEG has not been adequately explored in patients with olfactory impairment. We have shown that short ISIs can be used in olfactory EEG, in patients of varying olfactory function. Abstract: Use of chemosensory event-related potentials (ERPs) is limited by relatively poor signal-to-noise ratios (SNRs). We hypothesized that by reducing the standard inter-stimulus interval (ISI), the increased number of trial repetitions possible may increase SNR. In order to further investigate this, we performed the largest study to date assessing chemosensory ERP using short and long ISIs in 101 participants of varying olfactory function. Using rose odor (phenylethylalcohol, PEA) as a relatively selective olfactory stimulant, we found no significant difference in the proportion of individuals in whom ERPs were recorded using short or long ISIs. This was true in normosmic, hyposmic and functionally anosmic individuals. We also demonstrated significantly increased SNR using short PEA-ISIs, in the normosmic and functionally anosmic groups. Comparing between groups of different olfactory function, hyposmic patients achieved faster onsets and greater amplitudes than normosmics under the PEA-10s protocol. This could be due to increased stimulus attendance, but requires confirmation with further research.